Trehalose Contributes to Gamma-Linolenic Acid Accumulation in Cunninghamella echinulata Based on de Novo Transcriptomic and Lipidomic Analyses - Li, Shue; Yue, Qiang; Zhou, Shuai; Yan, Jing; Zhang, Xiaoyu; Ma, Fuying (Frontiers in Microbiology, 2018)
Gamma-linolenic acid (GLA) is essential for the well-being of humans and other animals. People may lack GLA because of aging or diseases, and thus, dietary supplements or medical reagents containing GLA-enriched lipids are in demand. Cunninghamella echinulata is a potential GLA-producing strain. Interestingly, we found that the GLA content of C. echinulata FR3 was up to 21% (proportion of total lipids) when trehalose was used as a carbon source, significantly higher than the 13% found when glucose was used. Trehalose is quite common and can be accumulated in microorganisms under stress conditions. However, little information is available regarding the role of trehalose in GLA synthesis and accumulation. Our study aimed to understand how the metabolism of C. echinulata responds to trehalose as a carbon source for GLA and lipid biosynthesis. We profiled the major sugars, fatty acids, phospholipids, and gene transcripts of C. echinulata FR3 grown in trehalose medium with glucose as a control by de novo transcriptomics, lipidomics and other methods. The results showed that trehalose could influence the expression of desaturases and that the GLA proportion increased because of delta-6 desaturase upregulation. The increased GLA was transferred to the extracellular environment through the active PI ion channel, which prefers polyunsaturated acyl chains. At the same time, trehalose might prevent GLA from peroxidation by forming a trehalose-polyunsaturated fatty acid (PUFA) complex. Our study provides new insights into the functions of trehalose in GLA accumulation.